Towards Sustainable Pro-Poor Development? A Critical Assessment of Fair Trade Gold. (10th June 2018) - Hilson, Gavin; Gillani, Alvina; Kutaula, Smirti
Abstract: This paper reflects critically on the progress made towards implementing Fair Trade gold programs capable of empowering subsistence artisanal miners in developing countries. Drawing on interviews with 'ethical' jewellers and officials at certification bodies, the very parties which have conceived and are ultimately driving these initiatives, it is argued that despite being projected as 'pro-poor', schemes are not empowering, nor in many cases even targeting, impoverished mining groups. Further analysis reveals that officials at certification bodies are chiefly responsible for this. Many have used stories of poor miners to engage 'ethical' jewellers enamoured with the idea of potentially alleviating poverty in developing countries through purchasing gold that can also be traced to the source. The case study reinforces claims that what constitutes 'fair' differs markedly throughout the supply chain. Highlights: Reflects critically on recent developments made to bring Fair Trade gold to market. Surveys the views of jewellers and certification bodies on the impact of Fair Trade gold. Surveys the views of jewellers and certification - bodies on the challenges with empowering small-scale gold miners. Reveals that the story being told to customers purchasing jewellery is very different to the reality. Offers explanations for why this is the case.